Identifying Key Components of Teaching and Learning in a STEM School. (May 2015) - Morrison, Judith; Roth McDuffie, Amy; French, Brian
<x xml:space="preserve">Abstract</x> This study was conducted at an innovative science, technology, engineering, and mathematics high school, providing a rich contextual description of the teaching and learning at the school, specifically focusing on problem solving and inquiry approaches, and students' motivation, social interactions, and collaborative work. Data were collected through interviews with teachers and students, classroom observations, school meetings, school design and planning efforts, student surveys, and student standardized test scores. We saw that the teaching and learning at the school were typically inquiry and problem based and that student motivation, collaboration, and social interactions were strong due to the environment of inquiry and problem‐based teaching and learning.